Inteligencia emocional y satisfacción marital en trabajadores de la unidad educativa Jorge Álvarez. Píllaro,2019 - Mendoza Carrillo, Maricela Beatriz, Verdezoto Aguilar, Jessenia Liseth (2020)
This research had the objective of analyzing the levels of emotional intelligence and marital satisfaction in workers of the “Jorge Álvarez” Educational Unit. The methodology is based on the quantitative approach, using two psychometric tests: Trait Meta-Mood Scale (TMMS-24) and the Marital Satisfaction Scale (MSS), or ESM in Spanish. The study was carried out in a population of 56 adults in a couple relationship, aged between 29 and 59 years. The statistical analysis was carried out using the Microsoft Excel software. With regard to EI: in the Care subscale, 32% of men and 27% of women correspond to an appropriate level; in the Clarity subscale, 36% of men and 34% of women correspond to an appropriate level; and, in the Repair subscale, 34% of men and 29% of women correspond to an appropriate level. With respect to the SM: in the Satisfaction with Marital Interaction subscale, 30% of men and 27% of women correspond to the medium level; in the Satisfaction subscale with the emotional aspects of the spouse, 27% of men and 23% of women correspond to the medium level; and, in the Satisfaction subscale with the organizational aspects of the spouse, 34% of men and 23% of women correspond to the medium level (higher percentages). It is concluded that men experience a higher level of Emotional Intelligence and Marital Satisfaction. Through Ch2, the relationship was determined into two significant subscales: attention - emotional aspects of the spouse; and, repair - marital interaction, concerning the study variables.